O transposon piggyBac: quantificando sua mobilização - Kaminski, Valéria de Lima (2015)
In this work we presented the idea to perform excision assays using the piggyBac transposable element as enzyme supplier and the inverted terminal sequences of the element, both necessary for mobilization of a transposable element. Drosophila S2 cells were electroporated to perform insertion of two different plasmids in the cytoplasm of cells, a plasmid carrying the terminal inverted repeats of piggyBac element flanking a GFP gene and other with the transposase coding sequence enzyme which recognizes the terminal inverted repeats, excise of the region where the element is and insert it into another locus. This is a vector-helper system, in which a fragment is excised from a plasmid with the help of the transposase located in the other. Conventional PCR was used to verify excision events showing a 200bp amplification region where the fragment was excised and a region 3kb amplification reagion at times when the fragment was full, ie, it has not mobilized. The qPCR technique was used to quantify the excision of this fragment, carrying out comparisons of the amount of plasmid DNA recovered from the S2 cells after the end of experiment with serial dilutions of the original plasmids carrying the ITRs, which was used as standard. The results showed that the technique involving electroporation and qPCR is feasible and can be used to quantify mobilization of transposable elements. Paralleling with existing tools for this type of quantification, qPCR shows up as a very sensitive technique of detection mobilization, as well as a low cost technique budget.